ChemInform Abstract: Acid‐Controlled Generation of Indans and Oxazolines from β‐Hydroxyarylethanamide. Issue 33 (25th July 2013) - Suresh, Rajendran; Muthusubramanian, Shanmugam; Boominathan, Muthusamy; Manickam, Govindaswamy
Abstract The reaction course can be controlled by the use of either TfOH or TiCl4 to produce indans or oxazolines, respectively.